Detection and identification of blood-borne infections in goats in Nigeria using light microscopy and polymerase chain reaction - Anise N Happi; Deborah M. Buba; Paul E Oluniyi; Kazeem Akano (International Journal of Veterinary Science and Research - Peertechz Publications, 2020)
Haemoparasitisms in animals are known to impose substantial economic burdens on owners. In Nigeria, most laboratories utilize only Light Microscopy (LM) for their diagnosis. Hence there is a need to have an update assessment of haemoparasitism of goat in Nigeria using molecular investigation.  Using LM, blood samples from a total of 173 goats in Ibadan were screened for haemoparasites and haemocytopathological evaluation. Among them, 126 blood samples were randomly selected and PCR tested for the 18S rRNA gene of Babesia/Theileria spp (B/T) and the 16S rRNA gene of Anaplasma/Ehrlichia spp (A/E), while 91 samples were evaluated for the 16S RNA of hemotropic mycoplasma (hemoplasma). Relationship between the haematological changes and PCR results was evaluated.  The PCR detection rate was significantly and more than 4-fold higher compared to LM (61.5% and 14.5%, respectively; P < 0.0001) alone. A total of 150 animals were tested by both methods with 62.7% overall infection proportion. Comparison of LM and PCR analyses showed approximately 50% misdiagnosis of Hemoplasma spp by LM with 82.7% and 100% false negative for A/E and B/T recorded by LM, respectively. The haemoparasites detected by LM were Borrelia spp, Hemoplasma spp, Babesia spp, Anaplasma spp and, Trypanosoma brucei. A total of 34.1%, 23% and, 51.6% samples were positive for B/T, A/E and, hemoplasma, respectively. Sequencing and phylogenetic analyses of some PCR products identified samples with high homology with Anaplasma ovis in the A/E group while the B/T were highly related to Theileria velifera. Sequencing of hemoplasma positive samples identified Mycoplasma ovis, Mycoplasma wenyonii and Pseudomonas fluorescens. The haematological changes were unspecific to infection types and, showed no significant deviation between haemoparasite positive and negative animals. The striking disparity between LM and PCR methods for haemoparasite detection and a larger repertoire of haemoparasites are presented. Borrelia spp, Mycoplasma wenyonii, Pseudomonas fluorescens and Theileria velifera are newly reported in goat with hemotropic mycoplasma being the most prevalent in Ibadan. Studies geared towards pathogenicity investigation in the unusual host, their diversity and factors of transmission are envisaged for effective prevention and control.